PP.20.16: CAROTID PULSE PRESSURE ASSESSMENT BY MEANS OF DIAMETER-VELOCITY LOOP. (June 2015) - Di Lascio, N.; Stea, F.; Bruno, R.M.; Bianchini, E.; Gemignani, V.; Ghiadoni, L.; Faita, F.
Abstract : Objective: Carotid pulse pressure (cPP) and carotid pulse wave velocity (cPWV) are increasingly used in clinical practice as biomarkers of cardiovascular disease. The diameter-velocity loop (lnD-V loop) could represent a valid approach for cPWV evaluation since it requires the use of the ultrasound equipment only. Aim of this study was to assess cPP from the elaboration of ultrasound images. Design and method: Common carotid artery ultrasound scans were obtained from 27 healthy subjects (44.1 ± 17.8 years, 44.4% males, BMI 25.5 ± 3.9 kg/m 2 ). The lnD-V loop was achieved plotting together diameter and flow velocity values obtained elaborating B-mode and PW-Doppler images. cPWV was assessed from the slope of the systolic linear reflection-free part of the loop which was determined identifying the points within the 20% and the 80% of the maximum velocity value (cPWV20/80) and, alternatively, locating the first peak of the Wave Intensity Analysis (WIA) (cPWVwia). Standard tonometric-derived carotid stiffness (CS) was also evaluated. cPP values were obtained from cPWV20/80 and cPWVwia calculations using the Bramwell-Hill equation (cPPbh-20/80, cPPbh-wia) firstly, and a model based on the Laplace law (cPPl-20/80, cPPl-wia) alternatively. A carotid pressure waveform was obtained linearly scaling the diameter instantaneous values according to cPP extreme values. cPP assessments and the corresponding pressure waveforms (Pbh-20/80, Pbh-wia, Pl-20/80, Pl-wia) were compared with the same parameters obtained by applanation tonometry (cPPton, Pton). Results: cPWV20/80 and cPWVwia values were in good agreement with CS assessments (r = 0.84 and r = 0.88, respectively). Comparison between cPPton calculations and cPPbh-20/80, cPPbh-wia, cPPl-20/80, cPPl-wia provided a correlation coefficient equal to 0.63, 0.81, 0.66 and 0.81, respectively. The biases obtained through the Bland-Altman analysis were all significant (-13.7 ± 13.1 mmHg, -11.2 ± 9.6 mmHg, -16.5 ± 12.4 mmHg, -14.2 ± 9.4 mmHg). Pbh-20/80, Pbh-wia, Pl-20/80 and Pl-wia were in good correlation with Pton (r = 0.94 ± 0.04 for all) while the root-mean square error values obtained were 9.4 ± 4.4 mmHg, 8.04 ± 3.5 mmHg, 10.01 ± 4.5 mmHg and 8.56 ± 3.9 mmHg, respectively. Conclusions: In addition to cPWV calculation, the lnD-V loop could also lead to a usable cPP evaluation. The best results were achieved calculating the cPWV through WIA and obtaining the cPP assessment using Bramwell-Hill equation.